Effectiveness of supply chain management (receiving and logistics) in 1st. Silicon (M) Sdn. Bhd. / James Jaol Matthew - Matthew, James Jaol (2006)
The study mainly captures on the Effectiveness of Supply Chain Management (Receiving and Logistics Section) in 1st. Silicon (M) Sdn. Bhd. in giving their service to the end-users. The end-users making orders through Purchase Order (PO) to purchase any goods that are used by them for their machines and equipments. These orders of goods will be forwarded to the suppliers or the vendors through Procurement section. When the suppliers or vendors received the PO, they will send the goods to the company through Receiving and Logistics section. Goods that are send out from the company back to vendor or to the customers will also have to go through the section. The researcher tried to find the problems and objectives of the project paper, and thereafter analyzed the significant of the study, which would benefit both Receiving and Logistics, the end-users and also the company. The general activities of the receiving and logistics were enhanced by the literature review that were collected either from the internal and the external sources which are relate to the receiving and logistics activities in the company. Research methodology described about the methods that are used by the researcher to collect data for the project paper. These data are collected from the internal end-users that have been selected as the respondents for the study. Finding and analysis that are conducted for the study were based on graphs which are extracted from the questionnaires that have been collected from the end-users or the respondents. Finding that have been concluded by the researcher found that services rendered by the receiving and logistics personnel were good, in which majority of the respondents satisfied and comfortable with it. Finally, from the data analysis and interpretations, conclusions and recommendations were derived. From the recommendations, receiving and logistics section and the end-users will have benefits in future and these would increase the level of efficiency for the section and it personnel.